2009
DOI: 10.3844/ajidsp.2009.307.313
|View full text |Cite
|
Sign up to set email alerts
|

Production and Roles of Glial Tissue Inhibitor of Metalloproteinases-1 in Human Immunodeficiency Virus-1-Associated Dementia Neuroinflammation: A Review

Abstract: Problem statement: Tissue Inhibitor of Metalloproteinases-1 (TIMP-1) and its cognate targets, the Matrix Metalloproteinases (MMPs), were differentially expressed in human brain samples with or without HIV-1 infection or HIV-1 Encephalitis (HIVE). Approach: A through literature review demonstrated that cell culture models of Central Nervous System (CNS) cell types had been used to illustrate the intricate temporal patterns of TIMP-1/MMP expression, regulated by a variety of inflammatory cytokines. Results: As M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…30 In addition, the neurotoxicity induced by Tat was inhibited by anti-MMP antibodies, but not by antibodies against Tat, indicating that Tat causes neuronal death through an indirect mechanism. 17 Our previous study indicated that Tat exposure upregulated MMP-9 protein levels in brain endothelial cells 14,15 and administration of Tat into the ICA enhanced MMP-9 activity in plasma and protein expression in brain tissue. 19 The mechanisms by which MMPs disrupt the barrier integrity of the brain endothelium appear to involve degradation of specific TJ proteins; therefore, it was surprising to show in the present study that the baseline Figure 5.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…30 In addition, the neurotoxicity induced by Tat was inhibited by anti-MMP antibodies, but not by antibodies against Tat, indicating that Tat causes neuronal death through an indirect mechanism. 17 Our previous study indicated that Tat exposure upregulated MMP-9 protein levels in brain endothelial cells 14,15 and administration of Tat into the ICA enhanced MMP-9 activity in plasma and protein expression in brain tissue. 19 The mechanisms by which MMPs disrupt the barrier integrity of the brain endothelium appear to involve degradation of specific TJ proteins; therefore, it was surprising to show in the present study that the baseline Figure 5.…”
Section: Discussionmentioning
confidence: 97%
“…16 In fact, it was showed that Tat-induced neurotoxicity can be prevented by an MMP inhibitor, prinomastat, and upregulation of TIMP-1 by glia in acute HIV-1 infection may exhibit neuroprotection. 17 Because targeting both PPAR and MMP activities may alleviate HIV-1-induced neuropathology, we focused the present study on the interactions of these factors in a model of HIV cerebral toxicity induced by HIV-specific protein Tat. Our data indicate that Tat-induced disruption of the blood-brain barrier (BBB), alterations in TJ protein expression as well as neuronal loss and astrogliosis can be attenuated by PPAR agonists and MMP-9 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that TIMP‐1 was down‐regulated by HCV. TIMP‐1 is an important marker for neuroinflammatory and neurodegenerative diseases . TIMP‐1 is known to aid cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Protection against a disrupted BBB in HIV‐1 infection has not been described well. An imbalance between MMPs and endogenous TIMPs (tissue inhibitors of MMPs) may contribute to HIV‐associated pathology by inducing a remodeling of the extracellular matrix . One study showed that Tat‐induced neurotoxicity can be prevented by an MMP inhibitor, prinomastat, and also that upregulation of TIMP‐1 by glia in acute HIV‐1 infection may exhibit neuroprotection .…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between MMPs and endogenous TIMPs (tissue inhibitors of MMPs) may contribute to HIV-associated pathology by inducing a remodeling of the extracellular matrix. 28 One study showed that Tat-induced neurotoxicity can be prevented by an MMP inhibitor, prinomastat, and also that upregulation of TIMP-1 by glia in acute HIV-1 infection may exhibit neuroprotection. 29 Recent studies indicate that natural sequence variations including SNPs in promoters and coding regions, especially nonsynonymous SNPs of the MMP genes, may result in the differential expression of MMPs in different individuals.…”
Section: Discussionmentioning
confidence: 99%